Export of Timber from Slovakia to China - Benda, Lukáš (2018)
Since globalisation plays a key factor in the pace of growth in international business, new possibilities of untraditional trades may arise. The thesis researches viability of Chinese timber market and most suitable approach of conducting export for “Lesprodukt” small to mid-size Slovak logging firm. For the research author used secondary sources coming from governmental and world organizations and as a primary source an interview with the director of the company. The investigation was conducted as an overall macro-economic analysis of the economies focusing on timber market and as investigation of process of exportation and importation for Slovakia and China, respectively. As a result, a list of recommendation and an outline of the process for conducting such operation is given.